You have the following expression:
9x² - 12x + 4
In order to factorize the previous expression, use the quadratic formula, given by:
![x=\frac{-b\pm\sqrt[]{b^(2)-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/7k7y3xb8tpc8g9j9690t1nd2zh42vpol1q.png)
where a, b and c are the coefficients of the polynomial.
In this case, you have:
a = 9
b = -12
c = 4
replace the previous values of the parameters into the quadratic formula:
![\begin{gathered} x=\frac{-(-12)\pm\sqrt[]{(-12)^(2)-4(9)(4)}}{2(9)} \\ x=\frac{12\pm\sqrt[]{144-144}}{18} \\ x=(12)/(18)=(2)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4wzj5cpeznumm70ew7beb3l2djtcagbp7j.png)
Hence, the factor of the given polynomial is:
(x - 2/3)(x-2/3)